Pelatihan Pembuatan Dokumen Penugasan dengan Konsep Mailmerge Pada SPS Mawar Indah Cempaka Putih Jakarta Pusat - Akmaludin, Akmaludin; Sihombing, Erene Gernaria; Rinawati, Rinawati; Ariswati, Ester (IAIN Syekh Nurjati Cirebon, 2024)
SPS Mawar Indah Cempaka Putih Central Jakartais an institution that handles education for student children which has the good aim of developing students who are noble, intelligent, pious and cheerful as well as making good quality children with personality, that there are problems that faced in the SPS Mawar Indah Cempaka Putih environment, namely how to provide improvements in the management of making assignment documents with the mailmerge concept to help improve their knowledge. We, from the Nusa Mandiri University Lecturers, who are assisted by a number of students through Community Service activities, provide solutions to overcome the problems faced by staff and teachers within the SPS Mawar Indah Cempaka Putih, Central Jakarta. This was done with the aim of providing full assistance and support to SPS Mawar Indah Cempaka Putih Central Jakarta in mastering management, especially in creating documents such as assignment letters with the mailmerge concept and features that complement other documents, such as letterheads, logos and images. which can support the success of SPS Mawar Indah Cempaka Putih. This treatment is given in order to ensure smooth development and advancement of education which is currently underway. The results of community service activities provide significant value with the good category gaining a weight of 61.41 for activity participants who have increased their experience and knowledge. Participants' progress scores were measured by filling in instrumentation in the form of a questionnaire via pretest and posttest using a direct ranking system method.